2007
DOI: 10.1109/tnn.2006.884676
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive WTA With an Analog VLSI Neuromorphic Learning Chip

Abstract: In this paper, we demonstrate how a particular spike-based learning rule (where exact temporal relations between input and output spikes of a spiking model neuron determine the changes of the synaptic weights) can be tuned to express rate-based classical Hebbian learning behavior (where the average input and output spike rates are sufficient to describe the synaptic changes). This shift in behavior is controlled by the input statistic and by a single time constant. The learning rule has been implemented in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…This device, thanks to its spike-based plasticity mechanisms, can be used in distributed multichip AER systems as a general purpose learning and classification module. VLSI implementations of spike-based learning systems have been previously proposed [15]- [21], but they either lack the combined memory encoding and memory preservation features of the spike-based plasticity mechanism implemented in this device, or cannot cope with highly correlated patterns as efficiently as the system described here. A recent alternative VLSI implementation of the same plasticity mechanism described in this paper has been proposed in [22].…”
Section: Hardware Implementationmentioning
confidence: 99%
“…This device, thanks to its spike-based plasticity mechanisms, can be used in distributed multichip AER systems as a general purpose learning and classification module. VLSI implementations of spike-based learning systems have been previously proposed [15]- [21], but they either lack the combined memory encoding and memory preservation features of the spike-based plasticity mechanism implemented in this device, or cannot cope with highly correlated patterns as efficiently as the system described here. A recent alternative VLSI implementation of the same plasticity mechanism described in this paper has been proposed in [22].…”
Section: Hardware Implementationmentioning
confidence: 99%
“…The NE community has recently developed efficient VLSI implementations of such types of computational modules: next to several designs of conductance-based and integrate-and-fire neurons [19,25,38,58,66], NE researchers proposed circuits that implement VLSI dynamic synapses [7], spike-based plasticity mechanisms [32,34,50,68], and soft winner-take-all (WTA) networks [16], for example.VLSI implementations of WTA networks of spiking neurons, with plastic dynamic synapse circuits are particularly important, because recent theoretical studies demonstrated that recurrent neural networks arranged in a way to implement soft WTA performance can implement critical aspects of cortical computation [57].…”
Section: Introductionmentioning
confidence: 99%
“…These technical constraints guided us in setting the network parameters of this chip in the CAVIAR system, a multichip spike-based vision system that classifies spatiotemporal trajectories [9], [42], [53], [54].…”
Section: Discussionmentioning
confidence: 99%